Diabetic ketoacidosis in children: an 11-year retrospective in Surabaya, Indonesia - Nur Rochmah; Muhammad Faizi; Netty Harjantien (Indonesian Pediatric Society, 2015)
Background Diabetic ketoacidosis (DKA) is a complication of type I diabetic mellitus (TIDM). Early recognition and prompt treatment can reduce mortality. Objective To evaluate the profiles of patients with diabetic ketoasidosis in Dr. Soetomo Hospital, Surabaya, Indonesia. Methods Retrospective medical records of patients admitted to the pediatric intensive care unit with DKA in Dr. Soetomo Hospital, Surabaya, Indonesia from January 2002 to June 2013 were reviewed. The data collected included clinical parameters, laboratory and imaging results, predisposing factors, complications and outcomes. Results During an 11 years period, there were 58 cases of DKA in children with T1DM. Eighteen subjects (31%) were boys. The severity of DKA was classified as follows: mild 13 (22.4%), moderate 23 (39.7%), and severe DKA 22 (37.9%). Recurrent DKA was diagnosed in 24 (41.4%) patients. Common clinical profiles recorded were dehydration 46 (79.3%), malaise 37 (63.8%), decreased consciousness 35 (60.3%), dyspnea 27 (46.6%), vomiting 26 (44.8%), fever 25 (43.1%), seizure 13 (22.4%), and decreased body weight 9 (15.5%). Laboratory results observed were as folllows: hyponatremia 19 (32.8%), hyperkalemia 12 (20.7%) and acute renal failure 3 (5.2%). Head CT scans showed that 2 (3.4%) patients suffered from cerebral edema. Infections, as triggers of DKA, were found in 12 (20.6%) patients: 4 caries and periodontitis, 3 urinary tract infections, 2 acute diarrhea, 2 acute pharyngitis, and 1 otitis externa. Four out of 24 patients with recurrent DKA failed to take their insulin dose prior to DKA. The average of length of patient stay in the PICU was 3.26 (SD 3.50) days. No patients died during the study. Conclusion Dehydration is the most common clinical profile of DKA in our study. More than half of the patients suffer from moderate to severe DKA.